Reply to 'gamma radiation measurement' - Ramli, Ahmad Termizi (Institute of Physics Publishing Ltd., 2006)
On page 441, Ramli et al make a statement that the Ludlum micro-R meter has an almost flat response to gamma radiation. I think this is unlikely, as the instrument is basically a simple sodium iodide scintillator based ratemeter with a fixed energy threshold. Such instruments generally have a response which varies considerably over the range of interest for environmental dosimetry. This ranges from the highest significant energy generated, 2.615 MeV from Tl-208, down to the lowest energy which is likely to escape from bulk material as a consequence of Compton scatter, around 60 keV. As an example, the response of a 38 mm × 55 mm sodium iodide detector varies over a range of 10 from Co-60 (1.25 MeV) to 109 keV when used in the gross count mode. The range varies by a factor of 2 between Co-60 and Cs-137 (662 keV), which are reasonably close to K-40 at 1.46 MeV and the 609 keV line from Bi-214, both of which are, or can be, major contributors to environmental gamma dose rates. This is with a much bigger detector than the one employed by the authors. Moving to a smaller detector, such as the 25.4 mm × 19 mm one in the Thermo 41 detector, the energy response varies by a factor of 30 from 87 keV to 1.25 MeV, with a Cs-137/Co-60 ratio also of 2. The detector in the instrument used is likely to have a range of response somewhere between the two.